Leaf Epidermis of Indian Bamboos Part. I-Dendrocalamus Nees - Chauhan, Laxmi; Bisen, S. S.; Agrawal, S. P. (Indian Forester, 1988)
A systematic study of leaf epidermis of Indian bamboos was undertaken under light microscope for facilitating their identification based on epidermal features. The present paper deals with 10 spcies of the genus Dendrocalamus Nees. Epidermal features of diagnostic value have been tabulated and illustrated through photomicrographs.